Christ as King and Kings as Christ - Depold, Jennifer (Medieval sermon studies, 2020)
This article examines the specific image of a knightly Christ applied to historical kings, in two late medieval sermons. The article situates these examples within the context of contemporary textual representations of kingship, both in sermons generally and in the ‘mirrors for princes’ genre. My aim is to contextualize and thereby understand the purposes of the two sermons which present a distinctive representation of kingship. With only these two known examples, this instance of the Christ-knight is a minor but important strand of the motif, and impacts the way in which scholars should consider both Christocentric devotion and notions of late medieval kingship.